Cariprazine Use in Combination With a Mood Stabilizer in First Episode Mania - Palacios-Garrán, Roberto; Llorca-Bofí, Vicent; Arteaga-Henriquez, Gara; del Agua, Enrique (Frontiers in Psychiatry, 2022)
Background: Cariprazine’s efficacy and safety have been previously tested in adult patients with acute mania associated with bipolar I disorder, but there is no available data in FEM. The objective of this study is to assess the efficacy and safety of cariprazine in combination with a mood stabiliser in treating FEM as well as to evaluate patients’ adherence to the treatment. Methods: FEM patients were recruited from the acute inpatient unit at Lleida University Hospital Santa Maria, between January and June2021. Their symptoms were evaluated using the Young Mania Rating Scale (YMRS) and the Clinical Global Impressions–Severity (CGI-S) scale at admission and at discharge. Akathisia was assessed using the Barnes Akathisia Rating Scale. Patient adherence to medication treatment was assessed 30 days after discharge using the Morisky, Green and Levine Medication Adherence Scale. Socio-demographic and clinical information were further collected. Results: Eleven patients with FEM were involved, seven women and four men. Their mean age was 26.00+/-6.37 years. Mean hospitalisation was 17.36+/-4.7 days. Cariprazine was combined with a mood stabiliser: lithium in seven patients and divalproex in four. Mean YMRS change from baseline was -24.55+/-7.5 and the mean CGI-S change from baseline was -2.55+/-0.82. Regarding adverse events, two (18.2%) patients presented with akathisia. At the 30-day treatment-adherence assessment, six (54.5%) patients were adherent and four (36.4%) had moderate adherence. Conclusion: In this sample, cariprazine in combination with mood stabilisers proved to be safe and effective in the treatment of FEM with more than half the patients being adherent to treatment.